2013
DOI: 10.1111/vco.12067
|View full text |Cite
|
Sign up to set email alerts
|

Tumour‐associated macrophages are associated with vascular endothelial growth factor expression in canine mammary tumours

Abstract: Tumour-associated macrophages (TAMs) have been implicated in carcinogenesis including an important role in angiogenesis. In this study, we describe the relationship between TAMs and angiogenesis in canine mammary tumours (CMT). Formalin-fixed paraffin-embedded CMT samples [(n = 128: malignant (n = 97) and benign (n = 31)] were submitted to immunohistochemical staining to detect MAC387, vascular endothelial growth factor VEGF and CD31 expression. A statistical analysis was carried out to assess possible associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
43
3
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(55 citation statements)
references
References 50 publications
7
43
3
2
Order By: Relevance
“…Some studies from veterinary oncology report that in canine mammary tumors proinflammatory mediators produced by the tumor-infiltrated inflammatory cells correlate with progression and angiogenesis [20, 5254]. In accordance, we show in dog mammary tumors a positive association between infiltrating CD3 + T-cells, VEGF, and microvessel density, implying that CD3 + T-lymphocyte cytokines in this type of cancer may stimulate angiogenesis through the induction of the proangiogenic VEGF.…”
Section: Inflammatory Cells and Sustained Angiogenesissupporting
confidence: 90%
See 2 more Smart Citations
“…Some studies from veterinary oncology report that in canine mammary tumors proinflammatory mediators produced by the tumor-infiltrated inflammatory cells correlate with progression and angiogenesis [20, 5254]. In accordance, we show in dog mammary tumors a positive association between infiltrating CD3 + T-cells, VEGF, and microvessel density, implying that CD3 + T-lymphocyte cytokines in this type of cancer may stimulate angiogenesis through the induction of the proangiogenic VEGF.…”
Section: Inflammatory Cells and Sustained Angiogenesissupporting
confidence: 90%
“…Similarly to human breast cancer, in canine mammary cancer the macrophages also polarize toward the M2 phenotype [57]. Recently, we and others demonstrated that TAM infiltration is significantly associated with VEGF expression in malignant canine mammary tumors and that genes involved in angiogenic cellular pathways have been significantly upregulated in macrophages cocultured with canine mammary tumor cell lines [20, 58]. …”
Section: Inflammatory Cells and Sustained Angiogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…The number expressed for CD3+ T-lymphocytes and for tumour-associated macrophages (TAMs) represents the mean value ± standard error of mean following a methodology previously used. 31,33…”
Section: Quantification Of Immunoreactivitymentioning
confidence: 99%
“…Os dados encontrados em literatura quanto a expressão de TAM e de eosinófilos, bem como a sua participação na angiogênese tumoral e progressão tumoral são conflitantes (LEEK et al, 1996;TAKANAMI et al 2002;TATAROGLU et al 2004;TSUTSUI et al, 2005;UTRERA-BARILLAS et al, 2010;KROL et al, 2011;GOLLAPUDI et al, 2013;RAPOSO et al, 2013;SUYANI et al, 2013;YURI et al, 2014). Além da análise dos TAMs, a adição de outros parâmetros como a análise de expressão VEGF e densidade microvascular, poderia auxiliar na investigação do envolvimento dos macrófagos ao processo de vasculogênese.…”
unclassified